Biocompatibility assessment of wearable C/TPU/Tegaderm strain sensors - Abu Hassan Zahri, Nur Nazihah; Nordin, Anis Nurashikin; Mohd Mansor, Ahmad Fairuzabadi; Ab Rahim, Rosminazuin; Md Ralib @ Md Raghib, Aliza 'Aini; Suhaimi, Muhammad Irsyad; Lim, Lai Ming (IEEE, 2023)
The rapid advancement of wearable technology has sparked significant interest in developing innovative sensors that can seamlessly integrate with the human body. Strain sensors have been widely used in wearable devices for human motion detection. The choice of materials for the substrate and electrodes of the strain sensors plays a crucial role in determining their biocompatibility. Existing wearable strain sensors commonly utilize polymeric films and planar structures, leading to restricted airflow in the area of attachment. Consequently, this limited ventilation can potentially elevate the risk of skin irritation, and bacterial infections, and cause discomfort for the users. In this paper, a biocompatible strain sensor for wearable technology is presented. The strain sensor design is discussed and fabricated using the printing technique. The biocompatibility of the sensor is assessed by conducting cell morphology and cell viability analysis. The finding shows that the C/TPU/Tegaderm strain sensor is noncytotoxic and highly biocompatible after being exposed to HFF-1 cells. These biocompatible sensors are promising for safe use on human skin.